Association of Thyroid-Stimulating Hormone (TSH) Levels With the Prognosis of Patients Undergoing Heart Transplantation: A Retrospective Study - Wei, Jiajie; Zhou, Yingsheng (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To investigate the impact of TSH levels using a more stringent cutoff of subclinical hypothyroidism (i.e., TSH > 2.5 mIU/L) on the short-term complications and long-term prognosis in patients who underwent heart transplantation (HTx). Methods: This is a retrospective study of consecutive patients with end-stage heart failure (HF) who underwent HTx. They were divided into three groups: thyroid-stimulating hormone (TSH) ≤ 2.50 mIU/L (L-TSH), 2.50 < TSH ≤ 4.91 mIU/L (M-TSH), and TSH > 4.91 mIU/L (H-TSH). The outcomes are all-cause death and cardiogenic death. Results: There are 63 (70%) males and 27 (30%) females. Nine (10%) patients died within 1 month after surgery, including five cardiogenic deaths. By 1 year, a total of 19 patients total were dead. The survival rate in the M-TSH group was significantly higher than that of the L-TSH group (P = 0.017). After adjusted by variables of sex, age, BMI, diabetes history, hypertension history, the multivariable Cox analysis showed that body mass index (HR = 0.804, 95%CI: 0.680–0.951, P = 0.011), and L-TSH (HR = 8.757, 95%CI: 1.786–42.948, P = 0.007 vs. M-TSH), and H-TSH (HR = 6.427, 95%CI: 1.137–36.327, P = 0.035 vs. M-TSH) were independently associated with all-cause death. The multivariable Cox analysis showed that body mass index (HR = 0.703, 95%CI: 0.564–0.878, P = 0.002), and L-TSH (HR = 17.717, 95%CI: 1.907–164.607, P = 0.011 vs. M-TSH) were independently associated with cardiogenic death. Conclusion: For patients with end-stage HF undergoing HTx, low and high baseline TSH levels are independently associated with 1-year all-cause death and low baseline TSH levels with cardiogenic death.